2019
DOI: 10.1097/ajp.0000000000000670
|View full text |Cite
|
Sign up to set email alerts
|

The Multimodal Assessment Model of Pain

Abstract: Objectives: Pain assessment is enigmatic. Although clinicians and researchers must rely upon observations to evaluate pain, the personal experience of pain is fundamentally unobservable. This raises the question of how the inherent subjectivity of pain can and should be integrated within assessment. Current models fail to tackle key facets of this problem, such as what essential aspects of pain are overlooked when we only rely on numeric forms of assessment, and what types of assessment need to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(62 citation statements)
references
References 99 publications
(120 reference statements)
2
59
0
1
Order By: Relevance
“…Optimal treatment of pain requires balancing both objective and subjective assessments of pain and can prevent long-lasting complications in a post-surgical population. Overreliance on objective pain scales, without incorporation of clinicians’ and patients’ subjective assessments, can increase patient anxiety and diminish the therapeutic alliance among patients, family members, and their healthcare providers [ 21 ]. However, overreliance on subjective assessments can introduce conscious or unconscious bias into a clinician’s assessment, as has been documented in studies investigating racial [ 22 ] and gender-based [ 23 ] prejudice in the treatment of pain.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal treatment of pain requires balancing both objective and subjective assessments of pain and can prevent long-lasting complications in a post-surgical population. Overreliance on objective pain scales, without incorporation of clinicians’ and patients’ subjective assessments, can increase patient anxiety and diminish the therapeutic alliance among patients, family members, and their healthcare providers [ 21 ]. However, overreliance on subjective assessments can introduce conscious or unconscious bias into a clinician’s assessment, as has been documented in studies investigating racial [ 22 ] and gender-based [ 23 ] prejudice in the treatment of pain.…”
Section: Discussionmentioning
confidence: 99%
“…The participants' pain narratives exhibit a diverse use of language; both elements of Wideman's 35 pain expression (pain narrative and pain behaviour) are evident in the transcripts. Rather than being observed, 'pain behaviour' was described by participants (such as rocking backwards and forwards).…”
Section: Discussionmentioning
confidence: 99%
“…The Multimodal Assessment Model of Pain (MAP) distinguishes between qualitative (words and behaviours) and quantitative (self and non-self-reported measures) assessments of pain 'and regards the qualitative pain narrative as the best available root proxy for inferring pain in others'. 35 Wideman et al describe 'pain expression' as 'the broad collection of qualitative words and behaviours that communicate pain'. They divide pain expression into two components: 'pain narrative', comprising words used to describe pain; and 'pain behaviour', which comprises nonverbal and para-verbal pain-related behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual patents also differ in their adeptness of communicating pain through numeric ratings, free speech dialog, pain maps [ 73 ], or standardized surveys. Different methods of collecting information about pain symptoms also tap into different aspects of the pain experience [ 74 ], such as quantitative pain measures (e.g., numerical rating), pain experience (e.g., unpleasant sensory or emotional experience), and pain expression (e.g., qualitative words, pain narrative, and behavior to communicate pain, pain behavior). We found that a combination of metrics was the most useful, with short versions administered more frequently and long versions administered about three times per day.…”
Section: Practical Considerations For Chronic Pain Dbs Trial Periomentioning
confidence: 99%